PERBANDINGAN APLIKASI ERP PADA PERUSAHAAN SKALA KECIL DAN MENENGAH DENGAN MENGGUNAKAN PARAMETER PRODUKTIVITAS BISNIS - Rayung Wulan (Faktor Exacta, 2010)
SAP, what is according to Gartner Dataques, occupying sequence 1(one) with the storey; level of market presentation, about 29% in the year 2005, big possibility will decrease by Microsoft Dynamics ( MD) by the end of 2010 waiting or possible quicker oppositely; also. Some report oppositely; also have mentioned that MD have got the revenue more than 4 times fold by the end of year 2006, far exceed SAP in same year. Globally is market for the price of US$ 17.8 billion one year, with the use by Middle and Small Scale industry (SKM) occupying sequence 3(three) non-stoped expand quickly, making SAP and MD compete tightly utilize to master the the market compartment. Comparison made technically between SAP and MD, but number mount the annual revenue of year 2006 the have given a few/little picture of how second ability the system ERP from consumer side. To test second of that system eat this article is divided by for 3 shares of is which first shares will be explained by base of whether/what that ERP, last at second shares will be explained by a second technical ability of the system. Comparison will be made direct between same. And conclusion will be placed in third shares. Comparison made by pursuant to literature got from various source and joining to become one. Keywords: ERP (Enterprise Resources Planning), SAP (System, Anwendungen, Produkte in Deratenverarbeitung), dan Businnes productivity